Risk factors associated to high pressure levels in university students - Celsiane da Silva Rodrigues Pereira; Mara Cristina Ribeiro Furlan; Aires Garcia dos Santos Junior; Larissa da Silva Barcelos; Anna Clara Freitas Maia (Universidade Federal do Ceará, 2020)
Objective: evaluating the association between risk factors and pressure levels in university students. Methods: descriptive, cross-sectional study, developed with 203 university students through a self-applicable questionnaire, built from the Ministry of Health instrument for the Telephonic Inquiry for the Surveillance of Risk Factors and Protection Against Chronic Diseases. The analysis of data was carried out using Kendall's tau coefficient. Results: 164 (80.8%) participants had normal pressure levels, nine (4.4%) had pre-hypertension, and 30 (14.8%) had hypertension. Regarding their lifestyles, 16 (7.9%) were smokers, 12 (5.9%) made abusive use of alcohol, 137 (67.5%) were active, 64 (31.5%) had abdominal adiposity, 29 (14.3%) were overweight or obese and 32 (15.8%) used salt in excess. Conclusion: the risk factors related to high pressure levels were being 35 years old or older, having abdominal adiposity, being overweight or obese.